(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article explains that theme parks are the main link of adventure tourism. The importance of the most famous theme parks and the income generated by these parks, the number of tourists visiting the theme parks, and the history of the theme park and its current status. Sections on the importance of theme parks and themed theme parks are described.